Physical Growth of Low-Birth-Weight Babies in First Six Months of Life: A Longitudinal Study in A Rural Block of Assam - Borah, Madhur; Baruah, Rupali (National Journal of Community Medicine, 2014)
Introduction: A longitudinal study was carried out in a rural block of Assam to assess the physical growth pattern of Low Birth Weight babies during their first six months of life and to compare the growth pattern with Normal Birth Weight counterparts. Methods: Total 30 LBW babies (0 -2 months) and equal numbers of NBW babies were randomly selected under five sub centres. They were followed up in monthly intervals till 6 months of age. Results: During the study period LBW infants had lower mean weight, length, head circumference compared to NBW infants. But LBW infants had higher rate of weight gain, increase in length and head circumference than the NBW infants. By 6 months of age 20% LBW babies caught up in weight and 30% in head circumference with NBW infants. 77% LBW infants remained underweight at 6 months of age (RR = 3.74). Conclusion: LBW babies had higher rate of weight gain during the first 6 months of age but still remained significantly lighter than the NBW infants.